IMPLICATIONS OF PARENTING PATTERNS FOR MIGRANT LABOUR'S FAMILY ON ACHIEVEMENT BEHAVIOR IN TEMBENG PUTIK VILLAGE - Zopiatul Fitriah (The Scientia Journal of Social and Legal Studies, 2022)
Tembeng Putik Village is one of 14 villages in Wanasaba sub-district which contributes the highest number of Migrant Workers. The condition of a migrant worker's family is clearly different from other families, because the head of the family (the father) works abroad, so that the care of children is entirely carried out by a mother. Parents have a very important role in shaping children's behavior, are responsible for children's education and meeting children's physical and emotional needs. Therefore, this study aims to reveal and explain the pattern of child cares in migrant workers' families and the things that encourage the application of parenting, and its implications for the child's achievement behavior. This study used a qualitative method with a descriptive approach. Data were taken through observation, interviews, and documentation. Data were analyzed by using Peter L Berger and Thomas Luckman's social construction analysis model, then achievement behavior was analyzed using McClelland's theory of achievement motivation. The results showed that the parenting which applied to the children of migrant workers' families was based on the experience of the agreement of both parents, the socio-economic conditions of the family, and the level of education of the mother as a single caregiver, it is called permissive parenting with the implication of child's behavior being unsatisfactory. This is because there is a will that does not have opportunities and undirected efforts, and also democratic parenting which has implications for the child's achievement behavior with the will such as becoming a doctor, bank employee, civil servant teacher and tourism agent in NTB. The will arises from the knowledge and opportunities that exist. This will is pursued through learning and planning that prioritizes education up to college (university).